Methodology for real impact assessment of the best location of distributed electric energy storage systems - Gonçalves, José António Ribeiro (2016)
Tese de doutoramento em Sistemas Sustentáveis de Energia, apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra